2017
DOI: 10.1155/2017/4385913
|View full text |Cite
|
Sign up to set email alerts
|

Late Ps. aeruginosa Inguinal Mesh Infection 12 Years after the Initial Operation: Report of the Case and Short Review of the Literature

Abstract: Inguinal hernia mesh repair is one of the most frequent operations performed worldwide. The Lichtenstein technique and its various modifications are the most popular operations for groin hernia repair. The rate of surgical site infection (SSI) following inguinal hernia repair ranges between 0 and 14% in various series. Most of these infections developed early postoperatively. The incidence of late mesh infection following open inguinal hernia repair still remains unclear and highly variable. Late deep mesh inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Virulence of the bacteria, the wound microenvironment and the bacterial load are thought to be associated with the possible deep seated mesh infections but havent been proved confidently. [6] Delikoukos et al has found no association between the use of prophylactic antibiotics and deep seated mesh infections. They said that the mesh material or the fixing materials also don't affect the SSI rate [3] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Virulence of the bacteria, the wound microenvironment and the bacterial load are thought to be associated with the possible deep seated mesh infections but havent been proved confidently. [6] Delikoukos et al has found no association between the use of prophylactic antibiotics and deep seated mesh infections. They said that the mesh material or the fixing materials also don't affect the SSI rate [3] .…”
Section: Discussionmentioning
confidence: 98%
“…[5] The SSI rate after inguinal hernioplasty has been reported between 0-14 %, however the reported infection rate by Lichtenstein in his own series was 0.003%. [6] Most of the infections are superficial SSIs which occur in the immediate post-operative period but the deep seated mesh infections, although very rare, are being reported too. The superficial SSIs are initially managed conservatively with the help of antibiotics and wound drainage and it is usually possible to salvage the mesh but deep infections causing the prolonged groin sepsis may require the removal of the infected mesh.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Filippou D reported a case of mesh infection in an inguinal hernia, 12 years after surgery. [ 15 ] Initially, conservative management with excision of sinus tract was done but sinus recurred and mesh had to be removed. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Initially, conservative management with excision of sinus tract was done but sinus recurred and mesh had to be removed. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ismail (2002), Chatzimavroudis (2014), Filippou (2017), Sohail (2004), Maheshwari (2016) reported case studies [9][10][11][12][13].…”
Section: Case Studiesmentioning
confidence: 99%